Hormone therapy in combination with radiotherapy in the treatment of prostate cancer: why and in which group of patients? - Milecki, Tomasz; Antczak, Andrzej; Kwias, Zbigniew; Milecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2015)
In recent years, significant development in the treatment of prostate cancer has taken place. One of the most documented methods of treatment in patients characterised by a high risk of progression is a combination of radiotherapy (RT) with long-term hormone therapy (HT). In this group of patients, neither RT alone nor HT alone allows satisfactory outcomes to be achieved, and therefore as monotherapy they are not recommended as optimal methods of treatment. In this review, we summarise arguments for combining radiotherapy with hormonal therapy in high-risk prostate cancer, with an emphasis on the results of phase III trials.